Pengembangan Bahan Ajar Teks Hikayat Berbantuan FlippingBook dalam Meningkatkan Higher-Order Thinking Skills (HOTS) untuk Siswa Kelas X Sekolah Menengah Kejuruan Al-Washliyah Sukoharjo Medan - Maulida Rahadian Hasri; Rita Rangkuti; Rika Kartika (Medan Resource Center, 2026)
This study was conducted to address the need for innovative teaching materials capable of fostering Higher Order Thinking Skills (HOTS) in learning hikayat texts. The study aimed to develop, validate, and evaluate the feasibility and effectiveness of FlippingBooks-assisted teaching materials for Grade X students of SMK Al-Washliyah Sukoharjo Medan. The research employed the Research and Development (R&D) approach. The results showed that the first and second material expert validations achieved scores of 85% (“appropriate”) and 90.6% (“very appropriate”), respectively, while the first and second media expert validations obtained scores of 98% and 97.3%, both categorized as “very appropriate.” The Indonesian language teacher assessment reached 84% (“appropriate”), and the field trial obtained 87% (“very appropriate”). The teaching materials also demonstrated an effectiveness level of 86% (“very effective”), indicating their potential to support the improvement of students’ HOTS through more interactive, technology-assisted learning. This study contributes to the development of digital teaching materials by integrating FlippingBooks to facilitate more engaging learning experiences while supporting the development of higher-order thinking in hikayat text instruction. Based on expert validation, teacher assessment, student responses, and effectiveness testing, the developed teaching materials are suitable and effective for classroom implementation.